Symbolic Pole Assignment of 2DoF Conventional Helicopter - Mumcu, Tarik Veli; Candir, Kutluhan Kursat; Ustoglu, Ilker (IEEE, 2017)
Unmanned air vehicles and their control is a popular research field. The next decade will determine the control perfection of this vehicles and their role in our daily lives will increase. The major advantages of the unmanned rotor systems can be given as their ability to hang on a particular altitude and their manoeuvre agility to move and escape. Whereas there are many studies of control of drones, quadrotors or conventional helicopter as well as full rank state feedback method, the studies considering combination of these methods are rare. Even in symbolic case it is either not detailed so that it can easily be followed and applied or missing. This study aims to assign the poles of two degree of freedom conventional helicopter. The pole placement method used here is full rank state feedback. Thus, the helicopter model for multi input multi output systems is explained, the stages of the control method are described and they are simulated with in Mathematica. The outputs and stability analysis illustrates the effectiveness of the study.
Keywords: State feedback; symbolic; full rank; 2 DoF helicopter; Computer Science